- Fes illegal housing and restructuring strategy – The state of the JNANATES - bousfiha, Sabah; Mohamed, Mounaji; Labyad, Jawad (Journal of natural sciences, life and applied sciences, 2020)
This research study aims to approach and identify the phenomenon of illegal housing in Fez by highlighting the most important factors and mechanism contributing to its origins, and then the most important stages it has learned, as well as the most important interventions and strategies the country has adopted for its structure. In order to approach this subject in an academic way, we have based on the curriculum, because of its importance in studying the various relationships and interactions between the accelerating rise of demographic growth due mainly to the natural increase of the population and rural migration, The rise in housing demand, while the old town was filled by the running-up of its property and the rise of the new city’s housing, brought about the emergence of the illegal housing phenomenon with the margins of Fez. We have also found the most important findings and recommendations in this study, which we include as follows: Despite the measures taken to find solutions to the problem of illegal housing in Fez, especially in the north-eastern part of the city, there are still several problems in the economic, social and environmental levels, and we suggest that: Integration of all the illegal neighbourhoods in Fez through its structure and the provision of various basic facilities. – reasonable support for the local community budget for its effective contribution to financing programs for the illegal housing restructuring, as well as for expanding its powers at the level of the intervention strategy. To reduce the overlapping of the competence of the actors in the field of structuring and to encourage coordination among them to make the operation a success. The State must be aware that the phenomenon of illegal housing is an inevitable reality and must, therefore, have the effective will to address it through the revitalization and support of economic and social housing programs with respect to quality factors in construction. To develop the city’s Susioeconomic projects in general, especially in illegal neighbourhoods, with a view to operating dormant units to contribute to financing the restructuring and housing programs. The increase in compensation for families living in buildings threatened with the collapse in return for empty-houses for rehousing. Support, development and evaluation of traditional activities with a view to achieving local development. -at the environmental level, encourage investment in creating green spaces consistent with the population. Participation of civil society in urban restructuring and rehabilitation projects. In order to accelerate the implementation of the plans and strategies adopted (village development strategy, human development projects, green plan... The aim of economic and social advancement for the rural world is to reduce or rather reduce rural migration toward the city.